Empowerment of Pregnant Women Through Education and Training on Breastfeeding Techniques for Breastfeeding Preparation and Exclusive Breastfeeding in Penyengat Olak Village, Muaro Jambi Regency - Enny Susilawati; Sari, Lia Artika (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
Breast milk is an excellent source of nutrition for infants, with a balanced composition that meets the growth needs of babies. The coverage of exclusive breastfeeding in Indonesia is still low. This community service aims to empower pregnant women through education and training on breastfeeding techniques in preparation for breastfeeding and exclusive breastfeeding in Penyengat Olak Village, Muaro Jambi Regency, in 2024. The community service activities will be carried out from January to October 2024. The implementation method involves empowering pregnant women through education, training, and demonstrations on correct breastfeeding techniques. This community service will also include demonstrations on proper breastfeeding methods. The tools used include educational materials on exclusive breastfeeding and breastfeeding preparation, a module on correct breastfeeding techniques, videos, a laptop, an LCD projector, stationery, and baby demonstration models. This empowerment activity successfully increased the knowledge and skills of pregnant women in Penyengat Olak Village. It is hoped that with this program, mothers can provide exclusive breastfeeding that positively impacts the health of both mothers and babies, as well as raise awareness about the importance of breastfeeding within the community.